Monitoring of adverse drug reactions to antidepressant drugs in a teaching hospital - Munoli, Swetha; Patil, Soumya B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions (ADRs) are considered among the leading causes of morbidity and mortality. Adverse drug reactions are important determinants of non-adherence to antidepressant treatment, but their assessment is complicated by overlap with depressive symptoms and lack of reliable self-report measures The present study was therefore undertaken to monitor the ADRs of the antidepressant in the psychiatric outpatient unit of Raichur Institute of Medical Sciences, Raichur, Karnataka, India Methods: Study was conducted from December 2012 to November 2013, the patients on antidepressant drugs from psychiatry out- patient department (OPD) of Raichur Institute of Medical Sciences were considered for analysis. The patients were diagnosed by consultant psychiatrist. Data was collected in standard questionnaire format. All patients diagnosed with psychiatric disorder as per ICD 10 criteria and receiving treatment with antidepressant were included. Assessment of causality and severity of recorded adverse events was done using WHO assessment scale and modified Siegel and Hartwig Scale respectively. Results: In our study 74 adverse drug reactions(ADRs) were seen among 52 cases, total 263 cases were screened.CNS and Anticholinergic side effects were most common adverse drug reactions noted. Tricyclic antidepressants (TCA) and Selective serotonin reuptake inhibitors (SSRIs) were the drugs causing maximum ADRs. Assessment of causality and severity of recorded adverse events showed possible to probable and mild to moderate severity respectively. Conclusions: CNS and Anticholinergic side effects were most common adverse drug reactions noted. Tricyclic antidepressants (TCA) were most commonly prescribed drugs followed by Selective serotonin reuptake inhibitors (SSRIs). Tricyclic antidepressants (TCA) and Selective serotonin reuptake inhibitors (SSRIs) accounted for most of ADRs (87.8%). Assessment of causality of recorded adverse events showed no certain cause and assessment of severity of recorded adverse events showed no severe cases.